2018
DOI: 10.22271/phyto.2018.v7.isp6.1.19
|View full text |Cite
|
Sign up to set email alerts
|

In silico docking and drug design of herbal ligands for anticancer property

Abstract: Innovation development and standardization of Novel Herbal Formulation(September 24-25, 2018)In silico docking and drug design of herbal ligands for anticancer property

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…With the recent development of technology, presently researchers are using computational methods to predict absorption distribution metabolism excretion (ADME) as well as toxicity profile of the constituents. In silico studies helps in the prediction of pharmacological targets which assists in the prediction of possible pathway of action (Waghulde, Kale, & Patil, 2018). Betulinic acid (BA), triterpenoid ADME study was conducted computationally with the help of PreADMET software by Khan et al, revealed that BA has good permeability from intestinal tissues but poorly permeable from skin, have good plasma protein binding.…”
Section: Pharmacokinetic Profiles Of Some Of the Reported Anti‐denguementioning
confidence: 99%
“…With the recent development of technology, presently researchers are using computational methods to predict absorption distribution metabolism excretion (ADME) as well as toxicity profile of the constituents. In silico studies helps in the prediction of pharmacological targets which assists in the prediction of possible pathway of action (Waghulde, Kale, & Patil, 2018). Betulinic acid (BA), triterpenoid ADME study was conducted computationally with the help of PreADMET software by Khan et al, revealed that BA has good permeability from intestinal tissues but poorly permeable from skin, have good plasma protein binding.…”
Section: Pharmacokinetic Profiles Of Some Of the Reported Anti‐denguementioning
confidence: 99%
“…But also the identification, extraction, and purification of the biologically active molecule from a particular plant is the most difficult task. In this manner, computational tools are used to eradicate these problems (6). Among all computational work, docking is one of the best methods because of the identification of active site between Ligand and Receptor in a 3D space which helps to find the biologically active molecule (7).…”
Section: Introductionmentioning
confidence: 99%